The Phenomenon of Teenage Pregnancy in the Philippines - Salvador, Jordan Tovera; Sauce, Ben Ryan Jucay; Alvarez, Marc Oneel Castillo; Rosario, Ahrjaynes Balanag (European Scientific Journal, ESJ, 2016)
Teenage Pregnancy had been a worldwide issue, and has raised large numbers of campaigns and awareness to lessen its occurrence. The total number of this phenomenon is increasing each year. Philippines is one of the Asian countries which shares similar situation. In a study conducted by the National Demographic and Health Survey in 2013, one out of every young Filipino women age 15 to 19 is already a mother or pregnant with a first child. Therefore, the government in partnership with the different nongovernment agencies should exert efforts in resolving this issue. Teenage Pregnancies are often associated with social development issues such as lack of sufficient education and poverty. This often results to single parenthood which catalyzes conditions that renders the mothers to become irresponsible. Hence, it conveys a social stigma in various countries and cultures. This study would like to focus on exploring the lived experiences of Filipino teenage mothers in their pre and post-natal stage on how they prepare and accept their new roles as mothers. The gathered data from the methods were analyzed and interpreted according to qualitative content analysis. As a result, this generated emergent themes which depicted the experiences of the participants.